Time in T.S. Eliot’s “Four Quartets: Burnt Norton” - Tamrakar, Milina (PT. Riset Press International, 2025)
The significance of time in Eliot’s “Four Quartets: Burnt Norton” is examined in this paper. Particular attention should be paid to “Burnt Norton,” the opening section of Eliots “Four Quartets”. This study examines Eliot’s treatment of temporality as a structural and thematic principle in contrast to previous scholarship that approached the Quartets through themes of music, dance, liturgy love, and salvation. I contend that Eliot views time as cyclical rather than linear with the past present and future constantly interacting to produce transcendental moments. Through recollection imagination and symbolic imagery like the rose garden echoes children’s laughter and the still point time is revealed in Burnt Norton as irredeemable yet essential. Speculative abstraction imaginative reconstruction ecstatic moments of stillness recognition of emptiness and reconciliation through words music and silence are the five movements that explore the interplay between temporality and timelessness in this poem. Through his engagement with Heraclitus, Heidegger Bergson, and Neoplatonic ideas Eliot positions time as a constraint as well as a window into eternity. Burnt Norton, the study concludes, enacts a paradoxical synthesis: temporal existence is unavoidable but the possibility of timeless order and meaning only arises through the memory of fleeting moments.